(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2024)
In this review, the methods of synthesis and applications of zinc oxide nanoparticles (ZnO NPs) were presented for the period from 2002 to 2024. Zinc oxide (ZnO) has a high economic value because of its inexpensive cost, natural availability, environmental friendliness, simple manufacturing process, and so on. ZnO has developed novel laser and optoelectronic device approaches that will increase the density of data storage and the speed of optical communication recording. Because of the changes in mechanical, chemical, and optical properties with decreasing size, that is generally assumed to arise from quantum confinement effects who is scale-dependent, there is a lot of research going on with ZnO, particularly in the area of nanotechnology. Low defect density ZnO nanostructures might be useful. Because their stress may be successfully regulated via flexible relaxation on free-side surfaces rather than plastic relaxation, nanostructures are more likely to generate faultless structures than epilayers.